Effect of salinity on embryo-larval development of yellow clam Mesodesma mactroides (Reeve, 1854) in laboratory - SANTOS,JUAN J.S. (2020)
Abstract Abstract: This study assessed the effect of salinity on embryonic development, larval growth and survival of the yellow clam Mesodesma mactroides in laboratory. Embryos and larvae of M. mactroides were submitted and maintained at four different salinities: 20, 25, 30 and 35 ppt, to determine optimal conditions for the species. Through descriptive analysis, the results showed that the embryos tolerate salinities between 25 - 35 ppt, presenting fast metamorphoses at salinities 30 and 35 ppt, during experimental period of 27 hours. The same tolerance pattern was observed in larval stage (25 - 35 ppt), showing a better development in salinity of 35 ppt. This result is verified in biometric analyzes of height and length of the shells and survival rate, with higher averages in treatments with salinity 35 ppt. The experimental period of this stage lasted 27 days, when the larvae were able to settle. These results indicate that embryos and larvae of M. mactroides tolerate salinities between (25-35 ppt), with the best growth and survival on high salinities being recommended to better yields in laboratory.